IMPLEMENTASI SISTEM INFORMASI DONASI MINYAK JELANTAH (SIMINAH) BERBASIS DIGITAL DI KOTA DUMAI DENGAN PENDEKATAN LEAN SOFTWARE DEVELOPMENT - Ramadhani, Shumaya Resty; Hanifah, Puja; Yuliska, Yuliska; Najwa, Nina Fadila; Hartanto, Boby; Syaliman, Khairul Umam (Politeknik Caltex Riau, 2024)
Used cooking oil, or waste cooking oil, is the byproduct of repeatedly using cooking oil, which results in the formation of substances harmful to the body. Furthermore, improper waste cooking oil management poses a risk of environmental pollution. To address this issue, PT. Kilang Pertamina Internasional Refinery Unit II Dumai (PT. KPI RU II), through its Corporate Social Responsibility (CSR) program, initiated the